2018
DOI: 10.1051/matecconf/201815603031
|View full text |Cite
|
Sign up to set email alerts
|

Bioleaching of trace metals from coal ash using local isolate from coal ash ponds

Abstract: Bioleaching of chromium, copper, manganese and zinc from coal ash were investigated using isolates from coal ash ponds particularly Psuedomonas spp. Six (6) different coal ash ponds were examined however, after initial screening Psuedomonas spp. were only present in three (3) coal ash ponds. Among the three coal ash ponds, results showed that eight (8) putative Pseudomonas spp. isolates were present that were identified using the Polymerase Chain Reaction (PCR). Using the eight putative Pseudomonas spp. for bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Therefore, most elements are encapsulated inside the core of the CFA. In light of this, using smaller particles in biometallurgical processes related to CFA is desirable [85,105].…”
Section: Grinding and Sievingmentioning
confidence: 99%
“…Therefore, most elements are encapsulated inside the core of the CFA. In light of this, using smaller particles in biometallurgical processes related to CFA is desirable [85,105].…”
Section: Grinding and Sievingmentioning
confidence: 99%
“…From the previous study [20], the optimum parameter obtained were 1% pulp density, speed of 90 rpm at 37°C and 5 mL initial inoculum. After 30 days of bioleaching, the maximum trace metal extracted were 13.77% Cr, 14.61% Cu, 6.33% Mn and 12.18% Mn.…”
Section: Bioleaching Kinetics: Shrinking Core Modelmentioning
confidence: 99%
“…The focus of this study is to investigate the rate controlling mechanism using Shrinking Core Model of trace metal extraction from coal ash using Pseudomonas spp. Based on the previous study [20], optimum conditions were used in the bioleaching process to obtain maximum extraction of trace metals.…”
Section: Introductionmentioning
confidence: 99%
“…citric, oxalic and maleic acids) produced by fungi/bacteria have the inherent capacity to leach out metals from resources by forming soluble metal–organic ligand complexes. Only a few studies have reported on the use of acidolysis by sulfuric acid produced by bacteria such as Acidithiobacillus thiooxidans or A. caldus . A maximum of 88% of Cu from low grade Cu‐oxide ores was extracted using the biogenic sulfuric acid produced by A. thiooxidans .…”
Section: Introductionmentioning
confidence: 99%